2019
DOI: 10.3390/met9080871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaF2 on the Viscosity and Microstructure of CaO–SiO2–Al2O3 Based Continuous Casting Mold Flux

Abstract: In this study, a CaO–SiO2–Al2O3-based continuous casting mold flux was designed using the FactSage thermodynamics software to determine the composition range of CaF2. The viscosity characteristics of the mold flux were determined using a rotating viscometer. The results show that the constant temperature viscosity at 1300 °C decreases gradually as CaF2 content is increased from 3% to 11% in the CaO–SiO2–Al2O3-based slag. Viscosity is reduced from 0.854 to 0.241 Pa·s, viscous the flow activation energy is reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Such a phenomenon is consistent with previous studies. [16][17][18][19][20][21][22][23][24][25][26] Physical properties of slags including viscosity intrinsically depend on ionic structure of molten slags. Therefore, to clarify the mechanism of fluorine (F) ions in decreasing slag viscosity, various spectroscopic instruments, such as nuclear magnetic resonance (NMR) spectroscopy, 42) Raman spectroscopy, 25,30) X-ray photoelectron spectroscopy (XPS) 22,43) and Fourier transform infrared (FTIR) spectroscopy, 44,45) as well as molecular dynamics simulation method [45][46][47] have been used to explore the effect of F ions on the structural changes of molten slags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a phenomenon is consistent with previous studies. [16][17][18][19][20][21][22][23][24][25][26] Physical properties of slags including viscosity intrinsically depend on ionic structure of molten slags. Therefore, to clarify the mechanism of fluorine (F) ions in decreasing slag viscosity, various spectroscopic instruments, such as nuclear magnetic resonance (NMR) spectroscopy, 42) Raman spectroscopy, 25,30) X-ray photoelectron spectroscopy (XPS) 22,43) and Fourier transform infrared (FTIR) spectroscopy, 44,45) as well as molecular dynamics simulation method [45][46][47] have been used to explore the effect of F ions on the structural changes of molten slags.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al 20) revealed that CaF 2 addition not only decreases the viscosity of low basicity SiO 2 -CaO-Al 2 O 3 -MgO silicate melts also changes the crystallization behavior from spherical diopside to plate-like anorthite. Wang et al 21) observed that the viscosity of CaO-SiO 2 -Al 2 O 3 -based low basicity mold fluxes decreases continuously with increasing CaF 2 content from 3% to 11%. Similar results were also obtained for low basicity mold fluxes by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining liquid becomes poor in Ca and F and richer in Na and Al as the cuspidine continues to grow in block-shaped morphology. The reduction of either F or CaF 2 results in a drastic increase in the viscosity of the remaining liquid [24]. Moreover, the increase of Al 2 O 3 also causes the significant surge in viscosity [25].…”
Section: Formation Of Sub-bandsmentioning
confidence: 99%
“…Fluorite (CaF2) is also considered a chemical species that decreases the viscosity of chemical systems. Two mechanisms of fluorite in silicates are described in Equations 19-20 [70][71][72]. There is a break in the structure by the action of fluorite, thus decreasing the viscosity of the chemical system.…”
Section: Fluoritementioning
confidence: 99%
“…There is a break in the structure by the action of fluorite, thus decreasing the viscosity of the chemical system. Fluorite decreases the viscosity of the chemical systems SiO2-Al2O3-MgO-MnO2-Fe2O3-Na2O-CaO-K2O-CaF2, CaO-SiO2-Al2O3-CaF2 [70], CaO-SiO2-MgO-CaF2 [71], CaO-SiO2-Na2O-Al2O3-MgO-CaF2-FeO-Li2O-B2O3 [72], CaO-SiO2, CaO-Al2O3-based mold flux [69] and in fluxes [59].…”
Section: Fluoritementioning
confidence: 99%